Pemetaan dan Sinergitas Kelembagaan Melalui Pemberdayaan Masyarakat di Desa Branjang Sebagai Desa Wisata Rintisan - Gana Wuntu; Pranoto Pranoto; Mukhamad Kholil Aswan (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2022)
The economy and the welfare of the community are the ultimate goals in tourism development as mandated in the Law of the Republic of Indonesia No. 10 of 2009 concerning Tourism. While Law no. 6 of 2015 concerning Villages states that the Village Fund is a strategic instrument to encourage community development and empowerment. Based on these two things, the management of tourism potential must be carried out by moving the nodes of village strength, both natural resources and human resources through village government arrangements that are clear and oriented towards the prosperity of the village community.